Sensors for the study of thermal properties of food - Шаповал, Світлана Леонідівна (Technology audit and production reserves, 2015)
The aim of the research was the development and testing of compact temperature sensor with fast response and minimal deviations which can operate on the main band of thermal processing of foodstuffs. Results of the work. There were formulated the main requirements to the temperature sensor for the study of the thermal characteristics of foodstuffs. There were analyzed the peculiarities of the use of common temperature sensors in the study of foodstuffs. It is also given the sensor circuit based on a semiconductor diode operating at a constant voltage mode. The choice of recording equipment for the work with the developed temperature sensor has been proved. Using the example of developed sensor and thermocouple of K-type there has been described the peculiarities of operating the sensors with open contacts in acide and alkaline medium. Linearity of the sensor in the temperature range of 55…95 ºC was proved. Scientific novelty. The equipment for continuons temperature control of products during the thermal processing was improved, technology of temperature fixing using a semiconductor diode has been further development. Practical value. Results of the development of temperature sensor of small size and with short response time allow to continuously record the temperature in separate parts of foodstuff that will promote optimal selection of thermal processing regimes.